EXPERT SYSTEM FOR STUNTING DETECTION IN TODDLERS USING DEMPSTER SHAFER METHOD - Apridonal M, Yori; Maharani, Dewi; Prayoga, J (STMIK Royal, 2024)
Abstract: Stunting is a chronic or chronic malnutrition that can be seen in the height of toddlers shorter than toddlers their age. the prevalence of toddlers affected by stunting nationally was 37.6 percent (2007) and decreased to 35.8 percent (2010). However, it increased to 37.2 percent (2013) and decreased again to 29.9 percent (2018). The data shows an erratic stunting prevalence. Many factors influence stunting, especially parents' knowledge about balanced nutrition that prevents stunting. Prevention of stunting needs to be done by monitoring nutritional status regularly and fulfilling balanced nutrition for toddlers. For early detection of stunting, an expert system using the Dempster Shafer method is needed. The Dempster Shafer method allows decision making based on various possibilities based on symptoms in toddlers. The results of the expert system calculation show that the Dempster Shafer method can detect stunting in toddlers by more than 90%. Keywords: dempster shafer; expert system; stunting Abstrak: Stunting yaitu kekurangan gizi menahun atau kronis yang dapat terlihat pada tinggi badan balita lebih pendek dari balita seusianya. pravelensi balita yang terjangkit stunting secara nasional sebesar 37,6 persen (2007) dan mengalami penurunan menjadi 35,8 persen (2010). Namun meningkat menjadi 37,2 persen (2013) dan menurun kembali menjadi 29,9 persen (2018). Data tersebut menunjukkan pravelensi stunting yang tidak menentu. Banyak faktor yang mempengaruhi stunting khususnya pengetahuan orang tua mengenai gizi seimbang pencegah stunting. Pencegahan stunting perlu dilakukan dengan pemantauan status gizi secara berkala dan pemenuhan gizi seimbang Balita. Untuk deteksi stunting sejak dini dibutuhkan seuatu sistem pakar menggunakan metode dempster shafer. Metode dempster shafer memungkinkan pengambilan keputusan berdasarkan berbagai kemungkinan berdasarkan gejala pada balita. Hasil perhitungan sistem pakar menunjukkan bahwa metode dempster shafer dapat mendeteksi stunting balita lebih sebesar 90%.Kata kunci: dempster shafer; sistem pakar; stunting